Disaster Awareness and Preparedness in Nigerian Polytechenic Libraries: A Survey - Owolabi, K. A.; Lawal, W. O.; Olukayode, Joseph; Pelemo, G. D.; Odenigbo, P. (Journal of Information and Knowledge, 2014)
The paper examined the disaster awareness and preparedness in Nigerian polytechnic libraries. A survey research design was used for the study. Purposive sampling was used to select one hundred and forty respondents from the library staff which include the academic staff and the non-academic staff. Questionnaire was used as the main instrument for gathering data. Findings revealed that that there is no disaster control plans in the polytechnic libraries under the study and the staff admitted that they were not preparing for disasters. Fire extinguishers were the common disaster equipment available in all the libraries. Lack of fund and disaster control plans were the major constraints facing the staff in creating awareness and preparing for disasters. The paper recommended that polytechnic managements should constitute disasters control committee in all the polytechnic libraries and at the same time disaster control plans should be made compulsory in all the polytechnic libraries as part of their working document.